IMPLEMENTASI METODE INKUIRI BERBASIS SCIENCE TECHNOLOGY SOCIETY MENINGKATKAN PRESTASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN SISWA KELAS X SMKN 1 MERBAU MATARAM - Ponidi Ponidi (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
Learning by applying the inquiry learning model based on science technologi society able to improve student achievement of Class X SMK N I Merbau Mataram in the subject of Civic Education. Improvement of student achievement is obtained from the evaluation conducted by researchers and collaborators. The results are seen in pre cycles of achievement learning that reached 64.3 increased to 68, 52 on cycle I, and 76, 03 on cycle II. In the pre cycle students who are passed reached 4 students (13%). In the first cycle, the passed students increased to 14 (46%), while in cycle II increased to 26 passed students (89%).